Prediction of fire evacuation in high-buildings junior high school using discrete event simulation - Firmansyah, Faisal Ibnu; Shofa, Mohamad Jihan; Winarno, Heru (Jurnal Teknika, 2024)
Indonesia is included in the category of countries with high disaster risk, including the risk of fire disasters. However, the lack of public awareness makes planning risks greater, such as physical losses, minor injuries, and even fatalities. Therefore, good mitigation is needed to reduce this risk. The research aims to propose disaster mitigation for fires in high-buildings. One thing that can reduce casualties is evacuation. The success of an evacuation can be seen from the evacuation time. The research locus is one of the elementary schools in Serang City with a two-story building. The Discrete Event Simulation (DES) approach is used when experiencing a particular event. The data taken is data on the number of students and teachers, data on evacuation times using stairs or vertical evacuation methods with a certain distribution according to actual data. There are 2 scenarios used in the simulation, namely (1) evacuation using the available stairs, and (2) evacuation using a combination of stairs for men and vertical evacuation tools for women. The evacuation system using stairs in the school building was not effective because it took 5.17 minutes, while the speed at which the fire spread was 4.30 minutes. Evacuation using scenario 2 - a combination of stairs and vertical evacuation chute - resulted in a faster evacuation time of 3 minutes. Thus, the results obtained provide a suggestion for carrying out evacuation using a combination of using stairs and using a vertical evacuation chute.